Implementation of a 4Pi-SMS super-resolution microscope - Wang, J; Allgeyer, ES; Sirinakis, G; Zhang, Y; Hu, K; Lessard, MD; Li, Y; Diekmann, R; Phillips, MA; Dobbie, IM; Ries, J; Booth, MJ; et al. (Springer Nature, 2020)
The development of single-molecule switching (SMS) fluorescence microscopy (also called single-molecule localization microscopy) over the last decade has enabled researchers to image cell biological structures at unprecedented resolution. Using two opposing objectives in a so-called 4Pi geometry doubles the available numerical aperture, and coupling this with interferometric detection has demonstrated 3D resolution down to 10 nm over entire cellular volumes. The aim of this protocol is to enable interested researchers to establish 4Pi-SMS super-resolution microscopy in their laboratories. We describe in detail how to assemble the optomechanical components of a 4Pi-SMS instrument, align its optical beampath and test its performance. The protocol further provides instructions on how to prepare test samples of fluorescent beads, operate this instrument to acquire images of whole cells and analyze the raw image data to reconstruct super-resolution 3D data sets. Furthermore, we provide a troubleshooting guide and present examples of anticipated results. An experienced optical instrument builder will require ~12 months from the start of ordering hardware components to acquiring high-quality biological images.